Recovery of polycyclic aromatic hydrocarbons and their oxygenated derivatives in contaminated soils using aminopropyl silica solid phase extraction. (November 2020) - Pulleyblank, Coren; Kelleher, Brian; Campo, Pablo; Coulon, Frederic
Abstract: The formation, fate, and toxicology of oxy-, hydroxy-, and carboxy- substituted PAH (OPAH, OHPAH, COOHPAH, respectively) alongside PAH in contaminated soils have received increasing attention over the past two decades; however, there are still to date no standardized methods available for their identification and quantitation in soil. Here we investigated and developed the first method using aminopropylsilica solid phase extraction (SPE) for these compounds. We further investigated the efficacy of the developed method for three soils representing a range of contamination levels and soil textural characteristics and evaluated the impact of different sample preparation steps on the recovery of targeted compounds. Average recovery of PAH, OPAH, and OHPAH standards were 99%, 84%, and 86%, respectively for the SPE method. In contrast, COOHPAH exhibited the lowest recovery (0–82%) and poor inter-batch reproducibility. Soil texture and contamination levels influenced full method efficiency. Specifically, soils with higher proportion of clay contributed to the loss of the higher molecular weight OHPAH prior to SPE. Soil with the highest contamination showed enhanced recovery of some lower-concentration mid weight PAH and OPAH, while the least contaminated soil showed greater sensitivity to evaporative losses during sample preparation. Recommendations for reducing matrix effects as well as the practice of using deuterated PAH surrogate standards for OPAH analysis are further discussed. Quantitation of recovered PAH and oxygenated PAH across the three soils showed high reproducibility (<10% relative standard deviation for a majority of compounds), supporting the use of this method for PAH, OPAH, and OHPAH at contaminated sites. Graphical abstract: Image 1 Highlights: Novel solid phase extraction (SPE) method using aminopropylsilica. Analysis of oxy-, hydroxy-, and carboxy- substituted PAH (OPAH, OHPAH, COOHPAH). Strong reproducibility for the quantitation of PAH, OPAH, and most OHPAH. Qualitative information for some COOHPAH and phenolic acids and aldehydes.